2009
DOI: 10.1517/17460440902821657
|View full text |Cite
|
Sign up to set email alerts
|

In vitromodels of pancreatic cancer for translational oncology research

Abstract: Background-Pancreatic cancer is a disease of near uniform fatality and the overwhelming majority of patients succumb to their advanced malignancy within a few months of diagnosis. Despite considerable advances in our understanding of molecular mechanisms underlying pancreatic carcinogenesis, this knowledge has not yet been fully translated into clinically available treatment strategies that yield significant improvements in disease free or overall survival.Objective-Cell line-based in vitro model systems provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 133 publications
1
21
0
Order By: Relevance
“…Additionally, the viability of pancreatic cancer stem cells is also dependant on sustained expression of SHh signaling. Thus, blockading the SHh signaling pathway with an inhibitor reduces pancreatic cancer growth and improves outcomes (19,48). Recently, we found that CCN1 functions in a similar pathobiological role in pancreatic carcinogenesis, indicating that CCN1 signaling is critical for epithelial-mesenchymal transition and stemness and is required to promote tumor growth by the side population (cancer stem cells) of pancreatic cancer cells in a xenograft model (7).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, the viability of pancreatic cancer stem cells is also dependant on sustained expression of SHh signaling. Thus, blockading the SHh signaling pathway with an inhibitor reduces pancreatic cancer growth and improves outcomes (19,48). Recently, we found that CCN1 functions in a similar pathobiological role in pancreatic carcinogenesis, indicating that CCN1 signaling is critical for epithelial-mesenchymal transition and stemness and is required to promote tumor growth by the side population (cancer stem cells) of pancreatic cancer cells in a xenograft model (7).…”
Section: Discussionmentioning
confidence: 98%
“…The importance of SHh signaling in the development of pancreatic cancer and chemoresistance has fueled intensive study on this signaling molecule (48). Ample evidence indicates that SHh signaling is one of the "underpinning" signaling pathways which is aberrantly overexpressed in virtually all PDAC and is associated with tumor growth, metastasis and less survival in a genetically engineered mouse model of pancreatic cancer and an orthotropic xenograft model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gemcitabine, a nucleoside analog that blocks DNA replication, remains the first line therapy for patients with advanced PCa. 7,8 The efficacy of gemcitabine over 5-fluorouracil, which had previously been the drug of choice, was based on a very modest increase in medium survival of less than 2 months. 9 Although erlotinib (EGFR inhibitor) has been approved by the FDA for PCa, it only increased survival by less than a month, when used in combination with gemcitabine.…”
Section: Introductionmentioning
confidence: 99%
“…The disease generally causes few or no symptoms, and diagnoses are typically made at an advanced stage, when only 1 in 5 patients is eligible for surgical resection (3). The average 5-year survival rates for this disease are less than 5%, and even in cases where surgery is possible, the rates rise to only 15% (2,4). In addition to surgical intervention, combination chemotherapy and radiation treatments are employed, but the highly aggressive and invasive nature of PDA leads to poor responses, and new innovative therapeutic approaches are in high demand.…”
mentioning
confidence: 99%